2001
DOI: 10.1088/0031-9155/46/12/313
|View full text |Cite
|
Sign up to set email alerts
|

The relative response of NE2561 and NE2611A ionization chambers in megavoltage x-ray beams

Abstract: The relative energy response of NE2561 and NE261 IA ionization chambers to megavoltage photon beams from the ARPANSA linac indicates significant differences between these two types of chamber. In 16 MV beams of TPR20(10) 0.779, differences of about 2% are observed. The results are expressed as ratios KQ of the beam quality correction factors kQ, where the kQ factor for each type of chamber is the ratio of the absorbed dose to water calibration factor ND, at the x-ray quality Q to that at 60Co. These results ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The change was made because of radiation damage causing cracks in the POM of the NE2561. Boas et al 21 reported that the relative responses of the NE2561 and NE2611 chambers differ by about 2%. However, follow-up measurements did not yield any difference in response at the 0.5% level.…”
Section: Iia Data Additional To Previously Published Resultsmentioning
confidence: 99%
“…The change was made because of radiation damage causing cracks in the POM of the NE2561. Boas et al 21 reported that the relative responses of the NE2561 and NE2611 chambers differ by about 2%. However, follow-up measurements did not yield any difference in response at the 0.5% level.…”
Section: Iia Data Additional To Previously Published Resultsmentioning
confidence: 99%
“…The five correction factors, k i , are summarized in Allisy-Roberts et al 19 and their values and uncertainties are given in table 3.…”
Section: The Nrc Standard Of Absorbed Dose To Watermentioning
confidence: 99%
“…These chambers are very similar, apart from design of the stem and the use of Delrin R (NE 2561) or aluminium (NE 2611A) for the chamber cap-retaining nut. The two chamber types are assumed to be equivalent in 60 Co radiation, although this may not be the case in other radiation beams 19 .…”
Section: Apparatus the Transfer Standard Ionization Chambersmentioning
confidence: 99%